Characterization of Ethanolic Extract of Streptomyces sp. as a Pancreatic Lipase Inhibitors Produced by Endophytic Streptomyces sp. AEBg12 - Lenni Fitri; Anja Meryandini; Dyah Iswantini; Yulin Lestari (Biosaintifika: Journal of Biology & Biology Education, 2017)
Endophytic Streptomyces sp. AEBg12 isolated from Zingiber cassumunar (Bangle) is known to produce pancreatic lipase inhibitory compound. However, the characteristics of this active compound has not been reported yet. This study aimed to determine the characteristics of pancreatics inhibitory compound produced by Streptomyces sp. AEBg12 and to assess the role of endophytic actinobacteria in producing pancreatic lipase inhibitor using endophytic-free bangle tissue culture, wild bangle and compared with the activity of Streptomyces sp. AEBg12 endophytes. Supernatant of Streptomyces sp. AEBg12 was extracted using ethanol, ethyl acetate, and n-hexane solvents. Toxicity test was performed using larvae of shrimp Artemia salina. The results showed that the best solvent to obtain pancreatic lipase inhibitor compounds was ethanol. Phytochemical analysis showed that ethanolic extract of endophytic Streptomyces sp. AEBg12 contained flavonoids. IC50 value of ethanol extract was 180.83 µg/ml. The result of TLC showed that ethanolic extract of Streptomyces AEBg12 had a blue luminescence band indicated that there were either flavone, flavanones, flavonols or isoflavones. Inhibitory activity of Streptomyces sp. AEBg12 was higher than wild bangle and bangle tissue culture. The information from this study can be be used as a basic data for further characterization of the active compound, which might be developed as an antiobesity agent through its pancreatic lipase inhibitory activity.